2015
DOI: 10.1111/and.12414
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ICAM-1 in impaired spermatogenesis after busulfan treatment in mice

Abstract: Expression of adherence proteins, such as P-cadherin, has been identified in the normal testis and changed in impaired testis induced by alkylating agents. Intercellular adhesion molecule-1 (ICAM-1), a member of the immunoglobulin superfamily of cell adhesion molecules, is a constituent component of the blood-testis barrier and a multifunctional molecule in homeostasis of spermatogenesis. However, the distribution of ICAM-1 in the testis of mice and expression changes after busulfan treatment remain unclear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…Our results found that MSC-secreted factors promoted ICAM-1,N-cadherin and P-cadherin expressions in vivo, suggesting maintaining BTB integrity and cell adhesion might be the significant way in the crosstalk of MSC and spermatogenic microenvironment. Immunolocalisation studies showed ICAM-1 to be present at Sertoli cells and germinal cells (Cai, Liu, Fang, Shen, & Xiong, 2016), particularly at the site of the BTB, coinciding with two critical cellular events that occur: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (Xiao et al, 2012). Immunolocalisation studies showed ICAM-1 to be present at Sertoli cells and germinal cells (Cai, Liu, Fang, Shen, & Xiong, 2016), particularly at the site of the BTB, coinciding with two critical cellular events that occur: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (Xiao et al, 2012).…”
Section: Msc-secreted Factor Therapy Attenuated Spermatogenic Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results found that MSC-secreted factors promoted ICAM-1,N-cadherin and P-cadherin expressions in vivo, suggesting maintaining BTB integrity and cell adhesion might be the significant way in the crosstalk of MSC and spermatogenic microenvironment. Immunolocalisation studies showed ICAM-1 to be present at Sertoli cells and germinal cells (Cai, Liu, Fang, Shen, & Xiong, 2016), particularly at the site of the BTB, coinciding with two critical cellular events that occur: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (Xiao et al, 2012). Immunolocalisation studies showed ICAM-1 to be present at Sertoli cells and germinal cells (Cai, Liu, Fang, Shen, & Xiong, 2016), particularly at the site of the BTB, coinciding with two critical cellular events that occur: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (Xiao et al, 2012).…”
Section: Msc-secreted Factor Therapy Attenuated Spermatogenic Cellsmentioning
confidence: 98%
“…P-cadherin primarily locates in peritubular myoid cells of the interstitial tissue of mouse testis (Lin & DePhilip, 1996). Immunolocalisation studies showed ICAM-1 to be present at Sertoli cells and germinal cells (Cai, Liu, Fang, Shen, & Xiong, 2016), particularly at the site of the BTB, coinciding with two critical cellular events that occur: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (Xiao et al, 2012). Ncadherin localises in spermatogonia, primary spermatocytes and Sertoli cells (Tsuchiya, Sato, Kameya, Okayasu, & Mukai, 2006).…”
Section: Msc-secreted Factor Therapy Attenuated Spermatogenic Cellsmentioning
confidence: 99%
“…There is growing evidence that busulfan treatment causes deleterious effects on cell junctions and the cytoskeleton. Intercellular adhesion molecule-1 (ICAM-1) is involved in impaired spermatogenesis after busulfan treatment in mice [ 15 ]. The expression of P-cadherin decreases when spermatocytes disappear after busulfan treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isto resulta no mau pareamento das bases resultando no bloqueio da replicação, transcrição do DNA e na inibição da proliferação e diferenciação celular (Iwamoto et al, 2004). Além disso, o bussulfano tem a capacidade de destruir os filamentos de vimentina que formam as junções justapostas entre as células de Sertoli afetando a estabilidade do nicho testicular das SSCs (Amann, 2008;Cai et al, 2016 (Blesbois, 2007;Kang et al, 2008;Song e Silversides, 2008). Consequentemente, a criopreservação de sêmen é atualmente o procedimento mais adequado para o banco de germoplasma em espécies aviárias (Blesbois, 2007;Woelders et al, 2006).…”
Section: Preparação Dos Receptores (Bussulfano)unclassified